Development of a physiological collagen architecture through anisotropic nanofibrous polycaprolactone-collagen scaffold for cartilage tissue engineering - Nobrega, Ana (2018)
In this study, we propose an innovative 3D electrospun scaffold with distinct biomimetic zones capable of both simulating the collagen fibrous architecture of the native cartilage and presenting mechanical features that show potential to be compatible with both static and dynamic cell culture protocols